Manual de los Reglamentos del Agua en Florida: Ley de Restauración de Cuencas de Florida - Michael T. Olexa; Luke D'Isernia; Laura Minton; Dulcy Miller; Sarah Corbett (EDIS)
Revised! This series is the Spanish language version of the Handbook of Florida Water Regulations by Michael T. Olexa, Luke D'Isernia, Laura Minton, Dulcy Miller, and Sara Corbett. Published by the UF Department of Food and Resource Economics, November 2006.